Single tumor-initiating cells evade immune clearance by recruiting type II macrophages - Guo, Xiaocan; Zhao, Yang; Yan, Huan; Yang, Yingcheng; Shen, Shuying; Dai, Xiaoming; Ji, Xinyan; Ji, Fubo; Gong, Xing-Guo; Li, Li; Bai, Xueli; Feng, Xin-Hua; et al. (Genes & development, 2017)
Tumor infiltrated type II (M2) macrophages promote tumorigenesis by suppressing immune clearance, promoting proliferation, and stimulating angiogenesis. Interestingly, macrophages were also found to enrich in small foci of altered hepatocytes containing liver tumor-initiating cells (TICs). However, whether and how TICs specifically recruit macrophages and the function of these macrophages in tumor initiation remain unknown due to technical difficulties. In this study, by generating genetically defined liver TICs, we demonstrate that TICs actively recruit M2 macrophages from as early as the single-cell stage. Elimination of TIC-associated macrophages (TICAMs) abolishes tumorigenesis in a manner dependent on the immune system. Mechanistically, activation of the Hippo pathway effector Yes-associated protein (YAP) underlies macrophage recruitment by TICs. These results demonstrate for the first time that macrophages play a decisive role in the survival of single TICs in vivo and provide a proof of principle for TIC elimination by targeting YAP or M2 macrophages.